EVALUATE EFFECTIVENESS OF ECO-ENZYME TO INHIBIT GROWTH OF CURVULARIA SP ISOLATED FROM DOG SKIN BY IN VITRO - Indriana, Ni Putu Tiara; Suartha, I Nyoman; Sudipa, Putu Henrywaesa (Buletin Veteriner Udayana; Vol. 15 No. 4 August 2023DO - 10.24843/bulvet.2023.v15.i04.p05, 2023)
Dogs are very susceptible to infected by fungal species. The fungus that is often found infected dogs is Curvularia sp. Herbal medicine that is believed to be antifungal are ecoenzymes. The ecoenzymes in this study were made from papaya skin (Carica papaya L.), soursop (Annona muricata L.), neem leaves (Azadirachta indica A. Juss) and lemongrass (Cymbopogon nardus L.). This study was carried out to evaluate the effect of ecoenzymes against the growth of Curvularia sp used quantitative methode with modification of agar plate diffusion (Kirby Bauer) with well diffusion technique. This study was experimental and used a completely randomized design with 6 treatments, ecoenzyme concentration 5%, 10%, 15% and 100%, positive control used itraconazole, and negative control used aquades. Data analysis used ANOVA and continued with the Games-Howell test. The result showed that the inhibitory zones at ecoenzyme consentration 5%, 10%, 15%, and 100% were 3,50 mm; 4,82 mm; 6,02 mm; and 8,85 mm, respectively. Ecoenzyme in this study could inhibited fungal growth because of the ingredient contain antifungal substance like alkaloid carpaine, terpenoid, azadirachtin, nimbin, nimbidin, sitronela, and geraniol and pH reducer, so Curvularia spp that grew well in range of 4.0-10 could inhibited.